Analisis Kemampuan Koneksi Matematis Siswa Pada Materi Persamaan Garis Lurus - Pangestuti, Windi Tri; Marlina, Rina (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research is qualitative descriptive research that aims to determine the ability of students' mathematical connections in solving problems in straight-line equation material. The subjects in the study were 17 students of class VIII junior high school. The test instrument used in this study was in the form of a description of 3 questions. Based on the test results, obtained the average results for question indicator 1 which was 85.7%, question number 2 with indicators using mathematics in other subjects obtained a presentation of 69.6%, and question number 3 with indicators connecting mathematics with daily life obtained a percentage of 30.3%. Meanwhile, the average percentage of mathematical connection compatibility of all students is 61.86%. Therefore, the mathematical connection ability of class VIII students in one of the junior high schools in the Karawang area is classified as moderate.